A stochastic theory of geographic concentration and the empirical evidence in Germany - Thomas Brenner (Max Planck Institute of Economics, 2005)
A stochastic model of the evolution of the firm population in a region and industry is developed. This model is used to make predictions about the expected probability distribution of the firm number in regions and their dynamics. Data on the spatial distribution of firms in Germany is used to check the predictions and estimate the parameters of the model. This is done for 196 industries separately.
Keywords: C12; L60; R12; 330; geographic concentration; industry dynamics; local clusters; empirical methodology